Mechanistic insights into the analgesic and anti-inflammatory effects of alcoholic extracts from Curcuma longa - Nagamani, N.; Sharmi, V. J.; Subash, K. R. (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Aim of the study was to scientifically validate the traditional Indian claims of Curcuma longa’s (turmeric) antinociceptive (pain-relieving) and anti-inflammatory effects. Methods: The alcoholic extract of C. longa was tested in three rodent nociceptive models: acetic acid-induced writhing: examines visceral pain, formalin test: evaluates both acute and chronic neurogenic and inflammatory pain and tail immersion test to assess thermal pain. The extract’s effects were compared to a control group and morphine (reference drug). Results: C. longa extract significantly reduced abdominal constrictions in the acetic acid test (59.36% inhibition). In the formalin test, the extract significantly decreased paw licking response time in both early (54.12% inhibition) and late phases (78.59% inhibition). C. longa extract significantly increased the tail flick reaction time in the immersion test, indicating pain relief. Conclusions: This study confirms the antinociceptive and anti-inflammatory activities of C. longa, providing scientific evidence for its traditional use in pain management.